Impact of grid size on uniform scanning and IMPT plans in XiO treatment planning system for brain cancer - Rana, Suresh (J Appl Clin Med Phys, 2015)
The main purposes of this study are to: 1) evaluate the accuracy of XiO treatment planning system (TPS) for different dose calculation grid size based on head phantom measurements in uniform scanning proton therapy (USPT); and 2) compare the dosimetric results for various dose calculation grid sizes based on real computed tomography (CT) dataset of pediatric brain cancer treatment plans generated by USPT and intensity‐modulated proton therapy (IMPT) techniques. For phantom study, we have utilized the anthropomorphic head proton phantom provided by Imaging and Radiation Oncology Core (IROC). The imaging, treatment planning, and beam delivery were carried out following the guidelines provided by the IROC. The USPT proton plan was generated in the XiO TPS, and dose calculations were performed for grid size ranged from 1 to 3 mm. The phantom containing thermoluminescent dosimeter (TLDs) and films was irradiated using uniform scanning proton beam. The irradiated TLDs were read by the IROC. The calculated doses from the XiO for different grid sizes were compared to the measured TLD doses provided by the IROC. Gamma evaluation was done by comparing calculated planar dose distribution of 3 mm grid size with measured planar dose distribution. Additionally, IMPT plan was generated based on the same CT dataset of the IROC phantom, and IMPT dose calculations were performed for grid size ranged from 1 to 3 mm. For comparative purpose, additional gamma analysis was done by comparing the planar dose distributions of standard grid size (3 mm) with that of other grid sizes (1, 1.5, 2, and 2.5 mm) for both the USPT and IMPT plans. For patient study, USPT plans of three pediatric brain cancer cases were selected. IMPT plans were generated for each of three pediatric cases. All patient treatment plans (USPT and IMPT) were generated in the XiO TPS for a total dose of 54 Gy (relative biological effectiveness [RBE]). Treatment plans (USPT and IMPT) of each case was recalculated for grid sizes of 1, 1.5, 2, and 2.5 mm; these dosimetric results were then compared with that of 3 mm grid size. Phantom study results: There was no distinct trend exhibiting the dependence of grid size on dose calculation accuracy when calculated point dose of different grid sizes were compared to the measured point (TLD) doses. On average, the calculated point dose was higher than the measured dose by 1.49% and 2.63% for the right and left TLDs, respectively. The gamma analysis showed very minimal differences among planar dose distributions of various grid sizes, with percentage of points meeting gamma index criteria 1% and 1 mm to be from 97.92% to 99.97%. The gamma evaluation using 2% and 2 mm criteria showed both the IMPT and USPT plans have 100% points meeting the criteria. Patient study results: In USPT, there was no very distinct relationship between the absolute difference in mean planning target volume (PTV) dose and grid size, whereas in IMPT, it was found that the decrease in grid size slightly increased the PTV maximum dose and decreased the PTV mean dose and PTV [Formula: see text]. For the PTV doses, the average differences were up to 0.35 Gy (RBE) and 1.47 Gy (RBE) in the USPT and IMPT plans, respectively. Dependency on grid size was not very clear for the organs at risk (OARs), with average difference ranged from [Formula: see text] (RBE) to 0.53 Gy (RBE) in the USPT plans and from [Formula: see text] (RBE) to 1.39 Gy (RBE) in the IMPT plans. In conclusion, the difference in the calculated point dose between the smallest grid size (1 mm) and the largest grid size (3 mm) in phantom for USPT was typically less than 0.1%. Patient study results showed that the decrease in grid size slightly increased the PTV maximum dose in both the USPT and IMPT plans. However, no distinct trend was obtained between the absolute difference in dosimetric parameter and dose calculation grid size for the OARs. Grid size has a large effect on dose calculation efficiency, and use of 2 mm or less grid size can increase the dose calculation time significantly. It is recommended to use grid size either 2.5 or 3 mm for dose calculations of pediatric brain cancer plans generated by USPT and IMPT techniques in XiO TPS. PACS numbers: 87.55.D‐, 87.55.ne, 87.55.dk